The Economic Implications of Non-Communicable Disease for India - Mahal, Ajay; Karan, Anup; Engelgau, Michael (World Bank, Washington, DC, 2013)
This report contributes to the literature on the economic implications of non-communicable disease (NCDs) in developing countries by focusing on the case of India. First, the authors examine available evidence on the economic impact of NCDs in India. Second, the authors present new estimates of impact of NCDs, both on household economic well being as well as on aggregate economic outcomes in India. India is a worthwhile case to study for many reasons, beginning with the large numbers involved. In the year 2004, an estimated 8.1 million Indians died from all causes. Based on WHO data on the distribution of deaths by cause, estimated deaths from non-communicable conditions (including injuries) amounted roughly to 4.8 million, or about 59.4 percent of all deaths in the year. Moreover, about 24 percent of these deaths from non-communicable conditions occurred in the 35-64 age groups as per data from medically certified deaths from hospitals located in urban areas of India. Available data also indicate that 34 percent of all injury-related deaths occurred among individuals in the 35-64 year age group. India's population is also ageing over time, an issue of concern given the higher incidence of NCDs in older age groups. All of these developments are occurring in a setting where health expenditures are growing rapidly led by an unregulated private sector and where health insurance and pension coverage are still limited. These financial concerns are further exacerbated by the emerging evidence that the India's poor are at heightened risk of acquiring NCDs owing to high rates of smoking and tobacco use, occupational risks, and residential living conditions.